Learning Brief: Lessons in Theory of Change from a Series of Regional Planning Workshops - Schuetz, Tonya; Förch, Wiebke; Thornton, Philip K.; Wollenberg, Eva Karoline; Hansen, James; Jarvis, Andy; Coffey, Kevin; Bonilla Findji, Osana; Loboguerrero Rodriguez, Ana María; Martínez Barón, Deissy; Aggarwal, Pramod K.; Sebastian, Leocadio S.; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This learning brief is part of a series to capture the process, progress and lessons from CCAFS in its endeavor to plan, implement and deliver research outcomes. Since the last of these learning notes was published1, the process for finalizing the impact pathways (IPs) was considerably simplified to ensure that it was as practical as possible and to ensure buy-in. This learning note describes that process, and the series of regional planning workshops; much of this work was focused on reducing the complexity of the IPs and their monitoring and evaluation (M&E) framework as far as was practicable